Reforma de los arts. 81 y 82 de la ley orgánica de la función legislativa, en relación al archivo del juicio político por parte de la comisión de fiscalización de la asamblea nacional - Coronel Sarango, Franz Alberto (2016)
Art 131 of the Constitution of the Republic of Ecuador said that "the National Assembly may proceed with the impeachment, upon request of at least one quarter of its members and for breach of the duties assigned to them by the Constitution and the law, of ministers or ministers of state, or the supreme authority of the Attorney General, Comptroller General, Attorney General, Public Defender, Public Defender General, superintendents, and members of the National Electoral Council, Court Electoral, Judicial Council and Council of Citizen Participation and Social Control, and other authorities determine that the Constitution during his tenure and for one year after completion. To proceed with the censure and dismissal favorable vote of the absolute majority of the members of the National Assembly, except the ministers or ministers of state and members of the Electoral Service and Judicial Council is required, in which case two-thirds is required. Censorship result in the immediate dismissal of the authority. If the reasons for censorship evidence of criminal liability arising, the matter will have to pass the knowledge of the competent authority." This arrangement allows the impeachment of the authorities here 7 indicated, which makes it a requirement for applying for a quarter of the members of the National Assembly, for breach of the duties assigned by the Constitution and the Law. The impeachment process ¡s performed by the rules says the Organic Law on the Legislative Branch, to which Article 80 of the Act provides that the Council of Legislative Administration, CAL, to verify compliance with the requirements and give to the proceeding. It is said that the Act provides for the Council of Legislative Administration, an attribution to verify requirements, without saying what would happen if you have not met them. The Article 81 of the Organic Law on the Legislative Branch, will mark the process stating: "The Committee on Oversight and Political Control, within five days avocet knowledge of the application and verified to comply with the provisions of Article 131 of the Constitution of the Republic, otherwise he filed. Described the process, notify the civil servant on the start of it, accompanying the request for prosecution and supporting documentation, so that within fifteen days to exercise its right to defense orally or in writing and present the exculpatory evidence it deems relevant." This provides that the Audit Commission states that verify eligibility requirements Application impeachment, otherwise I will file this if you have 8 not complied with the provisions of Art. 131 of the Constitution of the Republic of Ecuador, is in other words, if there are no signatures of the fourth part of the assembly. But the Audit Commission does not fit to file a request for impeachment, the wording of the constitutional provisions, because faculties to impeach an officer of the listed or referred to in Art. 131 of the Constitution, the Assembly not one of his organs. In this case the Audit Commission should forward the request proponents to proceed to complete and if not, to report to the House of the National Assembly through its president, to the effect that she decides. The Art. 82 of the Organic Law on the Legislative Branch that "expiration of the period of fifteen days mentioned in the previous article, the Committee on Oversight and Political Control shall submit, within five days, the President or Chairman of the National Assembly a report detailing-reasoned reasons why the proceeding filed or recommending impeachment. If deemed necessary, the Commission may request the President or President, an extension of up to five more days." Faculty oversight committee to give the reasons for which the process of impeachment is filed is established, allowing an organ of the Assembly and that it does not decide on the impeachment of a state official, which no legal effect because it conflicted with the constitutional provision.